Impact of care responsibilities on women's employment: a comparison between European and East Asian welfare states*. Issue 2 (15th March 2017) - Chou, Yueh-Ching; Pfau-Effinger, Birgit; Kröger, Teppo; Ranci, Costanzo
ABSTRACT: Women with care responsibilities tend to reduce their labour market activity and to work part time, even if there are cross-national differences. Empirical research often analyses this separately for childcare and elderly care, and studies are usually limited to Western societies. This article aims to explore to what extent women's care responsibilities for children and older people impact on women's labour market integration and how this impact differs in the context of different welfare states in Europe and Asia. The analysis is based on data from a new comparative survey for four cities (Jyväskylä, Hamburg, Bologna and Hsinchu) in four countries (Finland, Germany, Italy and Taiwan). While socio-economic and demographic factors (age, education, marital status, health, financial difficulty and cultural orientation) are considered, multinomial regression reveals that, concerning childcare, the differences are greater within Europe than between the European countries and the Asian welfare state included in the study. Moreover, it turns out that there is no association between caring for older relatives and female employment in any of the four societies. This study demonstrates that the impact of different types of care responsibilities on women's employment shows different directions and conditions in the context of different welfare states.